Proximal-to-distal sequencing and coordination variability in the volleyball spike of elite youth players: Effects of gender and growth - Serrien, B.; Goossens, M.; Baeyens, J.-P. (Journal of Motor Learning and Development, 2018)
The aim of this article was to examine changes in elite youth volleyball players` performance, proximal-to-distal sequencing, and coordination variability of the spike motion between the start and after 1 year of a talent development program. Eight boys and eight girls in late puberty/early adolescence were measured with 3D motion capturing for 2 consecutive years. Performance and performance variability increased and decreased, respectively, but both changes were not significantly correlated with growth. Gender differences were identified for proximal-to-distal sequencing, but a very strong similarity between both years was observed for all seven degrees of freedom (pelvis and trunk rotation, trunk flexion, shoulder horizontal adduction, shoulder internal rotation, elbow extension, and wrist flexion). The fact that this sequence was kept stable, despite marked growth effects, likely indicates that this sequence is biomechanically efficient and the motor control systems try to preserve it. Coordination variability was analyzed by coordination profiling with self-organizing maps. The decrease in coordination variability correlated strongly and significantly with increase in body height. Participants with stronger growth rates were observed to show smaller decreases in coordination variability, which possibly represents a mechanism to explore various coordination patterns to adapt to the more rapidly changing organismic constraints.